Prevalence of gastrointestinal helminths of sheep in Sherpur, Bangladesh - Poddar, Prianka Rani; Begum, Nurjahan; Alim, Md. Abdul; Dey, Anita Rani; Hossain, Md. Shahadat; Labony, Sharmin Shahid (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: Gastrointestinal (GI) parasitic infection is a prime cause of failures in sheep production. This study was conducted to ascertain the prevalence of gastrointestinal (GIT) helminths of sheep in Sherpur district, Bangladesh. Besides, prevalence of helminthiasis in sheep also assessed considering age, sex, nutritional condition and rearing system. Materials and methods: In total, 106 rectal fecal samples of sheep were randomly collected and were examined for the presence of ova by using direct smear and Stolls ova counting techniques during July to October, 2016. Eggs were identified on the basis of its size, morphology and other landmark features. Results: Out of 106 samples, 67.9% (n=72/106) revealed the presence of ova of different helminths. The prevalence of helminth infection was associated with Fasciola gigantica (11.3%; n=12/106), Paramphistomes (13.2%; n=14/106), Schistosoma indicum (3.8%; n=4/106), Moniezia sp. (3.8%; n=4/106), Strongyle-type (24.5%; n=26/106), hook worm (6.6%; n=7/106), Strongyloides sp. (12.3%; n=13/106) and Trichuris sp. (1.9%; n=2/106). Egg count per gram (EPG) was calculated which was ranged between 100 and 600. Parasitic counts in lambs, young and adult showed no significant variations (P=0.511) from one other. Infection was significantly (P=0.04) higher in poor body conditioned sheep (76.3 %) as contrasted to normal body conditioned sheep (57.4%). No significant variation (P=0.601) was noticed in infection rates between sexes. Females displayed a higher infection (70.0%) as compared to males (65.2%). In rearing system, the result was found statistically insignificant (P=0.247). Conclusion: Utterly, GI helminths are endemic at great levels among sheep in the study area. Also, their infestation differs within various age groups, sexes, nutritional condition and rearing system of sheep. http://doi.org/10.5455/javar.2017.d224